KECENDERUNGAN MINAT MAHASISWA PROGRAM STUDI KOMUNIKASI DAN PENYIARAN ISLAM (KPI) TERHADAP PROFESI JURNALIS - Hotna Sari; Heri Rahmatsyah Putra (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
This study aims to determine the tendency of students in the study program on Islamic communication and broadcasting STAI Ar-Ridho Bagansiapiapi to the profession of journalists. The method used in this study is the quantitative descriptive method with data analysis through a simple calculation of statistical data. Data collection techniques using observation guides, interviews, questionnaire guides and documentation. The results showed that the factors that influence the tendency of students from the Islamic Program for communication and broadcasting studies to the profession of journalists, there are individual (interpersonal) factors consisting of four indicators, namely indicators of the seriousness of the profession of journalism, will, attitude and activity in the conduct or follow-up of journalistic lectures in the Programme for communication studies and broadcasting of Islam has a percentage of 59.07% , of the four indicators with an average number of answers per question up to 62.96. Although environmental factors are divided into three indicators, namely care, pleasure and intensity in learning or driving has a percentage of 36.35% with an average number of responses per report of 37.03. The findings showed that the tendency of students of the Islamic Program for Communication and Broadcasting Studies towards the profession of journalist, 84 students have a strong tendency to the profession of journalists